Unseen Danger: Peripartum Cardiomyopathy in a Preeclamptic Mother with Irregular Antenatal Care at a Secondary Hospital in Jayapura, PapuaA Case Report and Literature Review - Theresia Herestuwito Naru; Kadek Yunior K; Henny Rumaropen (The International Journal of Medical Science and Health Research, 2025)
Introduction Peripartum cardiomyopathy (PPCM) is a form of dilated cardiomyopathy that occurs in the last month of pregnancy or within the first five months postpartum. Preeclampsia, characterized by hypertension and organ dysfunction, increases the risk of long-term maternal cardiovascular complications. Antenatal Care (ANC) has a key role in the early detection and prevention of conditions like PPCM in women with preeclampsia. Case Illustration:A 22-year-old primiparous woman presented with severe difficulty breathing, fatigue, and leg swelling. She had given birth 35 days earlier who had prior episodes of preeclampsia and intrauterine growth restriction (IUGR). Examination revealed lung crackles, murmur, a gallop heart rhythm, and pitting edema. ECG showed sinus tachycardia and right ventricular enlargement, while chest X-ray indicated cardiomegaly with pulmonary edema. Treatment consisted of diuretics, beta-blockers, fluid restriction, and ICU care. During her last pregnancy, she had experienced leg swelling since 37 weeks gestation but had irregular ANC visits, no obstetric ultrasound, and only took vitamins from a primary healthcare center. Discussion:This case highlights the association between preeclampsia and PPCM, a severe Peripartum cardiovascular complication. The patient exhibited classic PPCM symptoms, including shortness of breath, fatigue, and leg edema, with clear signs of cardiac dysfunction. A key factor was poor pregnancy monitoring, as she did not attend ANC regularly, leading to undiagnosed preeclampsia and its complications. Conclusion:PPCM is a serious cardiovascular complication related to preeclampsia. Regular ANC, including ultrasound screening and blood pressure monitoring, is essential to early detection and prevention of adverse maternal and fetal outcomes.